(untitled) - Edelstein-Keshet, Leah (New York, 1987)
The book discusses models into three broad categories: discrete, continous, and spatially distributed. The first describes populations that reproduce at fixed intervals; the second pertains to processes that may be viewed as continous in time; the last treats systems for which distribution over space is an important feature
Keywords: Biology; Mathematical models